Role of the misfit stress between grains in the Bauschinger effect for a polycrystalline material. (15th February 2015) - Chen, B.; Hu, J.N.; Wang, Y.Q.; Zhang, S.Y.; Van Petegem, S.; Cocks, A.C.F.; Smith, D.J.; Flewitt, P.E.J.
Abstract: The role of misfit stress in kinematic hardening under reversed straining of a Type 316H austenitic stainless steel has been investigated by using neutron diffraction combined with in situ deformation. Initial misfit stresses, often referred to an intergranular internal stresses, were created by the tensile pre-straining at high temperature. The misfit stresses at the length-scale of grain families, measured by neutron diffraction, were shown to be a function of the magnitude of the tensile pre-strain. The pre-strained specimens were further subjected to either continued (tensile) straining or reversed (compressive) straining at room temperature. In situ neutron diffraction measurements were undertaken to monitor the change of the misfit stresses during loading. The macroscopic stress–strain behaviour was used to derive isotropic and kinematic hardening stresses developed in the pre-strained specimens. Results show that the change of the transient softening stress towards a zero value is accompanied by a decrease in the change of the misfit stresses. A multi-scale self-consistent model has been developed to assist in understanding the measured change of the misfit stresses when subjecting the material to strain reversal. An important conclusion is that the origin of the kinematic hardening of Type 316H austenitic stainless steel arises from the misfit stress between grains.